Collaborative training: faculty and Library combat plagiarism: the case of the Instituto Superior de Contabilidade e Administração do Porto Library - Braga, Inês (2023)
The study focuses on plagiarism in higher education and on the need for collaborative work between students, faculty, and librarians to prevent it. The university library assumes a significant role as an information literacy training agent, transmitting the importance of an ethical use of Information and the respect for intellectual property and copyright laws. The literature review includes: a theoretical reflection on the concept of plagiarism; on plagiarism legislation; on how Higher Education Institutions—HEIs—cope and embrace training as a pre-emptive measure. In our capacity as faculty and as librarians at Porto Polytechnic Accounting and Business School—ISCAP—we conducted an empirical study on the library, applying a case study methodology, and documental research as data collection technique. This study mapped the Information Literacy training provided by the library over a period of seven years (2015–2021) in response to a strategic design to improve academic success and to make students aware of the correct use of scientific information. The results obtained demonstrate that the library already has a sustained training program, well-defined audiences, contents aligned with the objectives of the educational process, and a fruitful dialogue with faculty. Yet, this dynamic should be expanded in the future by a more systematic and diversified training offer.